التكوين العلمي لابن باديس وأثره التجديدي في مجال التعليم بالجزائر: (1913-1940 ): Educational Background of Ibn Badis and Its Regenerative Impact on the Field of Education in Algeria: (1913-1940) - Bensala, Youcef; Ali, Abdul Karim (Jurnal Fiqh, 2023)
The research seeks to discover the renewal brought by Ibn Badis to education in Algeria through the study of his personality, academic background, significant scientific achievements both within and outside Algeria, curriculum for education, and teaching methods that he discovered beneficial and efficient for learners. Furthermore, the research intends to shed light on how Ibn Badis overcame the obstacles and challenges caused by French colonization, which denied Algerian citizens access to all types of learning, especially Arabic and Islamic education. The study takes a historical approach by examining a sizable collection of texts and pictures that represent Ibn Badis’s vision for science and education. The research leads to the conclusion that Ibn Badis’s strong scientific foundation which he achieved under the guidance of specialized academics from numerous fields and countries, had a huge impact on improving his abilities and views of the world and increasing his sense of need to refresh and enhance the educational system of his country. Additionally, he set himself apart from his contemporaries and forebears by getting around France’s restrictions through the advantage of legal loopholes to prevent the use of violence, particularly during the planning and construction phases.